Old Macdonald had a Farm - Adams, Pam (Childs Play (International) Ltd, 1975)
An illustrated version of the traditional song describing the inhabitants of Old Macdonald's farm. Some pages are die-cut, permitting a portion of the next and previous illustrations to be seen.
Keywords: Juvenile literature- Non-Fiction